Trading mental and physical health in vestibular schwannoma treatment decision - Machetanz, Kathrin; Lee, Larissa; Wang, Sophie S.; Tatagiba, Marcos; Naros, Georgios (Frontiers in Oncology, 2023)
Objective: Observation, radiotherapy and surgery are treatment options in vestibular schwannomas (VS). Decision making differs between centers and is usually based on tumor characteristics (e.g., size) and the expected physical health (PH) outcome (i.e., hearing and facial function). However, mental health (MH) is often under-reported. The objective of the present study was to ascertain the impact of VS treatment on PH and MH. Methods: PH and MH were assessed in a prospective cross-sectional study including 226 patients with unilateral sporadic VS before and after surgical removal (SURG). Quality-of-life (QoL) was estimated by self-rating questionnaires: general Short-Form Health Survey (SF-36), Penn Acoustic Neuroma Quality-of-Life Scale (PANQOL), Dizziness Handicap Inventory (DHI), Hearing Handicap Inventory (HHI), Tinnitus Handicap Inventory (THI), and Facial Disability Index (FDI). QoL changes over time as well as predictive factors were accessed by multivariate analyses of covariance (MANCOVA). Results: In total, 173 preoperative and 80 postoperative questionnaires were analyzed. There was a significant PH deterioration related to facial function (FDI, PANQOL-face) after surgery. In line with facial rehabilitation, however, FDI improved within the first five years after surgery and did not differ compared to the preoperative patient cohort, eventually. In contrast, MH (i.e., PANQOL-anxiety) and general health (i.e., PANQOL-GH) improved with surgery and correlated with the extent-of-resection. Conclusions: Physical and mental health is significantly influenced by VS surgery. While PH might decrease after surgery, MH potentially increases when patient is cured. Practitioners should take MH into account before advising an incompletely VS treatment (e.g., subtotal resection, observation or radiosurgery).